PARENTING STYLES & INTERGENERATIONAL IMPACT: A GLOBAL BIBLIOMETRIC ANALYSIS - Abu Bakar, Azreen Zuhairi; Ishak, Mariyah; Yahaya, Nurul Faezah; Talib , Noor Husna (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Research on parenting styles and their effects across generations has been gaining notable international interest. However, detailed quantitative mapping of this academic field is still relatively underdeveloped. This bibliometric study was conducted to systematically examine worldwide research patterns, the intellectual foundations, and the thematic progression of parenting and intergenerational studies. Although there has been a steady rise in related publications, there remains a substantial gap in consolidating global findings and recognizing key trends and leading scholars in the field. To bridge this gap, a comprehensive search was carried out in the Scopus database using five primary keywords: Parenting, Intergenerational, Impact, Global, and Bibliometric. The search was carefully narrowed by applying inclusion criteria that focused on English-language journal articles published between 2020 and 2025, while excluding conference papers, books, and review articles. The data underwent cleaning and refinement using Open Refine, while Scopus Analyzer was employed to track productivity patterns. VOS viewer was used to visualize collaborative networks, keyword linkages, and citation structures. Out of an initial 2,006 articles identified, 523 met all selection requirements and were included in the final analysis. The findings indicate a sharp rise in research exploring the intergenerational influence of parenting styles, with substantial contributions from scholars in the United States, China, and the United Kingdom. Key focus areas emerging from the analysis include authoritative parenting, cultural factors, adolescent growth, and enduring behavioral impacts. Furthermore, the study uncovers the development of new interdisciplinary research themes that combine elements from psychology, sociology, and education. This bibliometric assessment provides critical insights for researchers, professionals, and decision-makers by offering a detailed overview of the global research landscape, pinpointing gaps in current knowledge, and proposing potential avenues for future investigation to deepen the understanding of parenting's long-term effects across generations.